Auditory Induced Vection: Exploring Angular Acceleration Of Sound Sources - Ivo Manuel Neves Rodrigues dos Santos (2019)
Vection effect is the body movement sensation, when there is no movement occurring. The main example given for this vection sensation is when someone is sitting in a stationary train and another train starts moving alongside of the stationary train where the perceiver is, providing an illusion of movement. Although this sensation is mostly associated with the visual system, studies demonstrated that brain has a movement-sensitive area in the auditory cortex and that it is possible to induce auditory vection. Related studies uses binaural reproduction, which has been shown to be effective on AIV. However, in this project, we aim to test factors of angular acceleration reproduced by an 8 speaker array, circularly disposed.